Frontiers of remote sensing information processing - Chen, C. H. (World Scientific, 2003)
This book examines advanced topics in remote sensing information processing, including signal and image processing algorithms, pattern recognition, and sensor data fusion. Key methodologies covered include neural networks, wavelet transforms, and knowledge-based systems. The content addresses SAR images, hyperspectral images, seismic analysis, automatic target segmentation, change detection, and image compression. Applications span microwave remote sensing, statistical pattern recognition, data mining, and military uses, with three chapters dedicated to seismic signal processing and discrimination.